A cross‐sectional study of health literacy in patients with chronic kidney disease: Associations with demographic and clinical variables - Une Elisabeth Stømer; Lasse Gunnar Gøransson; Astrid Klopstad Wahl; Kristin Hjorthaug Urstad (Wiley, 2019)
Abstract Aim The aim of this study was to investigate health literacy in patients with chronic kidney disease in a multidimensional perspective. Design A descriptive, cross‐sectional study. Methods Patients with chronic kidney disease at stages 3-5 were included in the study between February-August 2017 (N = 187). Health literacy was measured by the Health Literacy Questionnaire (HLQ). Multiple linear regression analysis was performed to identify associations between health literacy and demographic and clinical variables. Hierarchical cluster analysis was performed to identify characteristics of groups with high and low health literacy. Results Finding and critical appraise health information were the most challenging dimensions of health literacy. Female gender, lower level of education, greater number of prescribed medications and depressive symptoms were associated with lower health literacy. The group identified with lowest health literacy was further characterized by living alone and presence of comorbidity.